味覚刺激にて誘発された舌咽神経痛と三叉神経痛の同時発症の1例 - 浅香, 卓哉; 大賀, 則孝; 中村, 裕介; 北川, 善政; 坂田, 健一郎; 渡辺, 陽久 (日本口腔外科学会雑誌, 2022)
Glossopharyngeal neuralgia (GN) is a rare painful condition characterized by brief paroxysmal attacks in the glossopharyngeal nerve distribution. It is triggered by chewing, coughing, talking and swallowing. We report a rare case of combined trigeminal neuralgia and GN triggered by taste stimulation. A 63-year-old man was referred to our hospital with a complaint of sharp left mandibular and submandibular pain caused only by eating sour or salty foods. Computed tomography and sialography revealed a slight salivation disorder but no salivary gland disease. The symptom was not improved by salivary gland massage, and we then examined each pain area using the selective anesthesia test. As the symptoms were improved by topical anesthesia to the tongue root region, we made a diagnosis of GN. Furthermore, magnetic resonance imaging and angiography revealed compressions of the left glossopharyngeal nerve and left trigeminal nerve by the left anterior inferior cerebellar artery and left anterior superior cerebellar artery, respectively, based on which we diagnosed a combination of trigeminal neuralgia and GN. Treatment with carbamazepine relieved the pain favorably; however, the medication was discontinued due to drug eruption. Finally, we performed microvascular decompression for both nerves, after which the patient immediately experienced complete pain relief.